Association of individual psychopathology with family functioning in a Greek nonclinical sample. Issue 1 (2nd January 2019) - Adamis, Dimitrios; Petmeza, Ioanna; McCarthy, Geraldine; Tsibidaki, Assimina; Tsamparli, Anastasia
ABSTRACT: Family functioning is influenced by different factors like social context, qualitative characteristics, and an individual's medical or psychiatric condition. We examine the effects of sociodemographic factors and individual psychopathology on family functioning in a non-clinical sample. Cross- sectional study. Data were collected: age, gender, occupation, education, and description of the family, history and/ or presence of mental or physical illnesses, Family Assessment Device and Symptom Checklist-90-R. A healthy sample of 137 families with a total of 407 individuals was analysed. Multilevel analysis showed that individual psychopathology was the only significant factor for family dysfunction. Thus, there is a strong association between family dysfunction and psychopathology of a member.